Institutional Co-Creation Interfaces for Innovation Diffusion during Disaster Management - SOLOMON, Adrian; KETIKIDIS, Panagiotis; SIAVALAS, Felicia (Management Dynamics in the Knowledge Economy, 2017)
This paper discusses the concept of Resilient and Green Supply Chain Management (RGSCM) implementation in South Eastern Europe (SEE) from the point of view of understanding the structure of the inter-organizational (institutional) interfaces involved in this process as well as how are these interfaces evolving and transforming over time. As social and environmental concerns are growing in importance through normative and coercive directions, all the regional actors (triple/quadruple/quintuple helix) that supply chains interact with need to bridge their inter-organizational interfaces to properly ensure co-creation at the entire stakeholder level towards increasing the chances of a homogenous implementation of RGSCM. In this context, this paper adopts a three-stage mixed methodology of interviews, survey, focus groups, modelling and simulation case studies. The results show that the key pillars of inter-organizational interface integration and evolution reside in the proper identification of the key goals (performance indicators) of the involved institutions, which will maintain market-optimized competition levels. Then, institutions will steadily adhere to the market trends as explained by the ST and INT and in the process of adopting the RGSCM eco-innovation (DIT), the new entrant institutions will transform their inter-organizational interface to properly bridge with the core market stakeholder group. Finally, the key driver of interface alteration resides in the ability of disruptive (eco) innovators to set new standards. This research has core academic implications by extending the INT, DIT and ST under the context of RGSCM, policy implications in terms of proper policy making to support the required co-creation as well as practical implications by helping organizations to manage their inter-organizational interfaces.